Exploring the toxicity of cellulose nanofibrils in a lung epithelial cell line - Teixeira, Sara (2020)
Nanotechnologies and nanomaterials (NMs) applications have been growing in recent years, bringing benefits to society but raising also some concerns about their safety to human health. Cellulose is a natural material that fits the global trend of sustainability: ecological, low cost, abundant and renewable nature. In particular, cellulose nanofibrils (CNF)1 are forest-derived products with advantageous mechanical, optical and rheological properties, assuming a high industrial potential, e.g., in paper, food, pharmaceutical and biomedical industries. With the innovative applications expanding, CNF synthesis and production has increasing, leading to concerns about occupational exposure, particularly by inhalation, or consumers exposure. The toxicity studies of other NMs, like MWCNT, have had a major impact on the understanding of the nanofibres health effects on humans. MWCNTs have been reported to cause adverse effects in vitro and in vivo, such as DNA damage and oxidative stress2. Because CNF show a high resemblance in terms of aspect ratio to MWCNT, our main focus is to identify if some of the CNF synthesized have a genotoxic or carcinogenic potential. This study aims to assess the safety of two types of CNF produced with different pre-treatments (TEMPO-mediated oxidation and enzymatic hydrolysis) of an industrial bleached Eucalyptus globulus kraft pulp, through the characterization of its cytotoxicity and genotoxicity in human cells. The CNF cytotoxicity was assessed using lung epithelial alveolar (A549) cells by two methodologies, the MTT and the clonogenic assay, whereas the genotoxicity was assessed by the cytokinesis-block micronucleus assay. Dose-range finding experiments were performed using the MTT (24h, 48h and 72h exposure) and the clonogenic (8 days exposure) assays, which revealed that both CNF were not cytotoxic at concentrations between 3,125 and 100 μg/ml. On the contrary, both CNFs were able to increase cell viability at the highest concentrations tested (50 and 100 μg/ml). This effect had been previously observed in the same cell line exposed to CNF produced by TEMPO-mediated oxidation, but at the lowest concentration level3. The potential of the CNF to induce chromosomal alterations, either chromosome breaks or loss is being analysed through the micronucleus assay and the results will be presented. Overall, this study is expected to uncover potential adverse outcomes of CNF to human health, in order to promote the design of safer CNF and CNF-based products that will allow a more sustainable and responsible industrial development. References: 1) Gamelas, J., Pedrosa, J., Lourenço, A., Mutjé, P., González, I., Chinga-Carrasco, G., Singh, G. and Ferreira, P. (2015). On the morphology of cellulose nanofibrils obtained by TEMPO-mediated oxidation and mechanical treatment. Micron, 72, 28-33. 2) Louro, H., Pinhão, M., Santos, J., Tavares, A., Vital, N. and Silva, M. (2016). Evaluation of the cytotoxic and genotoxic effects of benchmark multi-walled carbon nanotubes in relation to their physicochemical properties. Toxicology Letters, 262, 123-134. 3) Ventura, C., Lourenço, A., Sousa-Uva, A., Ferreira, P. and Silva, M. (2018). Evaluating the genotoxicity of cellulose nanofibrils in a co-culture of human lung epithelial cells and monocyte-derived macrophages. Toxicology Letters, 291, 173-183.